The inter-device reliability of global navigation satellite systems during team sport movement across multiple days - Crang, Z. L.; Duthie, G.; Cole, M. H.; Weakley, J.; Hewitt, A.; Johnston, R. D. (Journal of Science and Medicine in Sport, 2022)
Objectives: (1) Determine the inter-device and inter-manufacturer reliability; and (2) investigate the variation in reliability over time for common global navigation satellite systems. Design: Repeated measures. Methods: A total of twenty 10-Hz devices manufactured by StatSports (n = 10, Apex Pro; StatSports, Newry, Ireland) and Catapult Sports (n = 10, Vector S7; Catapult Sports, Melbourne, Australia) were towed on a sprint sled during 8 40-minute team sport movement protocol over a 4-week period. The coefficient of variations for distance, velocity and acceleration/deceleration metrics were calculated to show dispersion of the data relative to the mean or median for each manufacturer and interpreted as good, 5%; moderate, <10%; and poor, coefficient of variation 10%. The coefficient of variation range described the variation in reliability and was interpreted as small, 5%;moderate, <10% and large, 10%. Inter-manufacturer agreement was represented as a Cohen d (95% confidence interval) standardised effect size. Results: Inter-device reliability for distance, peak velocity and average acceleration was good (coefficient of variation = 0.1 to 3.9%) for both manufacturers, with small variation across sessions. For most threshold-based acceleration and deceleration counts, StatSports devices showed good to moderate reliability, with moderate variation across sessions; Catapult showed good to poor reliability, with large variation across sessions. Inter-manufacturer agreement demonstrated moderate to very large effect sizes reported for most metrics. Conclusions: Reliability was suitable and consistent for measures of distance, velocity, and average acceleration. StatSports devices generally possessed suitable reliability and consistency for threshold-based accelerations and decelerations, though Catapult devices did not. Most metrics should not be compared between manufacturers.; Objectives(1) Determine the inter-device and inter-manufacturer reliability; and (2) investigate the variation in reliability over time for common global navigation satellite systems.